2008
DOI: 10.1016/j.brainres.2008.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial-dependent manganese neurotoxicity in rat primary astrocyte cultures

Abstract: Chronic exposure to excessive levels of Mn results in a movement disorder termed manganism, which resembles Parkinson's disease (PD). The pathogenic mechanisms underlying this disorder are not fully understood. Several lines of evidence implicate astrocytes as an early target of Mn neurotoxicity. In the present study, we investigated the effects of Mn on mitochondrial function. Primary astrocyte cultures were prepared from cerebral cortices of one-day-old Sprague-Dawley rats. We have examined the cellular toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
89
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 86 publications
9
89
0
2
Order By: Relevance
“…Shukla [9] have demonstrated a concentration-dependent effect of Mn on the brain microsomal Mg Apoptosis has been shown to be involved in Mn-induced neurotoxicity. Mn-exposure triggered apoptosis and cell death via the ERK signaling pathway [10]. The present study demonstrated that dietary Mn induced similar apoptosis in the brain region, as was observed following Mn administration in previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Shukla [9] have demonstrated a concentration-dependent effect of Mn on the brain microsomal Mg Apoptosis has been shown to be involved in Mn-induced neurotoxicity. Mn-exposure triggered apoptosis and cell death via the ERK signaling pathway [10]. The present study demonstrated that dietary Mn induced similar apoptosis in the brain region, as was observed following Mn administration in previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…The mechanism of neurotoxicity appears multifactorial. Astrocytic dysfunction occurs due to their high affinity transport system accumulating high intracellular concentrations of Mn (Yin et al, 2008). Manganese also causes microglial activation by induction of cytokines and reactive oxygen species (Dodd and Filipov, 2011), as well as causing disruption of several neurotransmitters and mitochondrial dysfunction, culminating in neuronal apoptosis (Smith et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Mn enters the mitochondria via a mitochondrial Ca 2+ uniporter (Gavin et al, 1999). Some of the mitochondrial dysfunction include altered mitochondrial respiration (Gavin et al, 1999), inhibition of mitochondrial aconitase activity (Zheng et al, 1998), loss of mitochondrial transmembrane potential (Malecki, 2001;Rao & Norenberg, 2004;Yin et al, 2008) and reduction of ATP (Milatovic et al, 2009;Roth et al, 2000). Inhibition of the mitochondrial electron transport chain by Mn (e.g.…”
Section: Manganesementioning
confidence: 99%